Evolution of antibiotic treatment in patients with tuberculosis: systematic review - Andrade, Nelson E.; Monroy , Emily S.; Párraga, Daver S.; Párraga, Angie S. (Revista Gregoriana de Ciencias de la Salud, 2024)
Tuberculosis, caused by the microorganism Mycobacterium tuberculosis, is a persistent infectious-contagious disease that continues to represent a significant challenge for health systems despite scientific advances in diagnosis and treatment. This study aimed to examine the historical evolution of antibiotic treatment of tuberculosis through a comprehensive literature review of relevant scientific articles obtained from academic databases such as PubMed, SciElo and Google Scholar. Four main areas were identified and analyzed: the chronology of the development of antibiotic treatments for tuberculosis, the clinical benefits derived from new antibiotics, current strategies to confront antibiotic resistance in tuberculosis, and future technological perspectives in diagnosis and treatment. Tuberculosis was highlighted as a continuing challenge to public health due to the emergence of strains resistant to conventional treatments.